Control structure design for a styrene manufacturing process. - Tay, Ying Hui. (2010)
The conventional approach for designing process control strategies for chemical plants has been to set production rates by fixing process feed rates followed by designing automatic control systems around each unit operation sequentially through the process. However, as processes become more complex with greater energy integration, the design of a plantwide control problem becomes very important in yielding robust control structures to keep the plant stable in the face of varying disturbances. An important component of control structure design involves the selection of controlled variables as they can significantly affect the resulting performance of the control structure. Therefore this thesis attempts to select controlled variables for a styrene manufacturing process by applying the Self-Optimizing Control principle proposed by Skogestad. The basis of selecting the controlled variables is such that holding the selected controlled variables constant leads to an acceptable economic loss when the plant is subjected to disturbances, thereby reducing the need for re-optimization. A detailed methodology of the application of self-optimizing control is presented for the styrene plant and the resultant control structure yielded a small loss of $5.2/h. This control structure is then evaluated and compared with previous control structures for styrene monomer plants.